An Analysis of Commuting Distance and its Controlling Factors in the GTHA - Yawar, Sadia (My University, 2016)
The increasing length of the daily commute is a major issue for many commuters in the Greater Toronto and Hamilton Area (GTHA). In order to alleviate this problem through policy, the policy makers require more in-depth understanding of this issue. This study explores different travel behaviour, socioeconomic and labour market determinants of commuting distance for resident workers in the GTHA, especially those having normal commutes and those having extreme commutes. This study also explores which areas of the GTHA are most self-contained, and what are the average commuting distances of each sub-region of the GTHA. The primary data source for this study was Transportation Tomorrow Survey (TTS) for the year 2011. Supplementary data were obtained from InfoCanada and Statistics Canada. Descriptive analysis in this study, focused at the Census Sub-Division (CSD), examined self-containment, outbound commutes, inbound commutes, resident employees and jobs densities, and average commute distances for place of residence and place of work. Study results showed that Toronto and Hamilton CSDs are the most self-contained areas in the GTHA, whereas areas located in the north and northwest of Toronto are major sources of outgoing commutes. Toronto and its adjacent CSDs have the lowest average commuting distance, whereas residents of Georgina and Brock commute exceptionally long distances. Multivariate regression analyses were applied to a disaggregate dataset (TTS). Workers older than 15 years of age living in the GTHA were divided into two major categories based on the length of their commute: (i) normal commuters (those having a mean commuting distance of 10.8 km) and (ii) extreme commuters (those having a mean commuting distance of 40.9 km). Factors affecting commuting distance for these two groups were examined. Similarly, residents living and working in the GTHA were divided into two categories: Resident workers living in (i) Jobs-rich areas or (ii) Resident-rich areas. Factors affecting commuting distance of these resident workers were also examined. The key controlling factors of commuting distance include gender, age, mode of transportation, employment status, ratio of jobs to employed residents, age of youngest child, auto availability in household, multi-worker household, median income, jobs and population density, and distance from CBD. Significant socioeconomic, travel behaviour and land use determinants for normal commute distances were also applicable to extreme commute distance. Transit was the preferred mode of transportation for long distance commuters in the GTHA, except for those living in job-rich areas. Workers associated with Sales and Service occupation and living in jobs-rich areas exhibited shorter commute than those in General/Clerical occupation. These findings are important to understand the changing travel patterns and behaviours of commuters in the GTHA. These results will be of interest to transportation planners, engineers, and policy makers as it highlights the inclination of long distance commuters to use transit.
Keywords: Commuting Distance; Extreme Commuters; Jobs-housing balance; Self-Containment; Urban Planning